Faktor-Faktor yang Berhubungan dengan Kunjungan Antenatal ke 6 (K6) - Sari, Marlynda Happy Nurmalita; Langoday, Lusia Paulina Lipa; Muyassaroh, Yanik; Nuryanti, Erni (Prodi DIII Kebidanan Blora Poltekkes Kemenkes Semarang, 2025)
In accordance with the Regulation of the Minister of Health of the Republic of Indonesia Number 21 of 2021, health services for pregnant women at least 6 times include: 1 (one) time in the first trimester, 2 (two) times in the second trimester; and (three) times in the third trimester. In 2022, in East Nusa Tenggara province, the achievement of K6 is 50.57% below the national target of 60% and the achievement of K6 at the Kalike Health Center is 55.0% below the target of the East Flores Regency strategic plan of 98%. The purpose of this study was to determine the factors associated with low antenatal visits to 6 (K6) at Kalike Health Center. Type of analytical survey research with a cross cectional approach, using chi-square data analysis. The population of this study was all III trimester pregnant women, the sampling technique was saturated sampling, the sample amounted to 31 respondents. The results showed that there was a relationship between maternal knowledge and K6 (pvalue = 0.0001), there was a relationship between maternal age and K6 (pvalue = 0.007), there was no relationship between maternal work and K6 (pvalue = 1,000), there was a relationship between maternal education and K6 (pvalue = 0.007). There was no maternal parity relationship with K6 (pvalue = 0.376), there was a relationship between maternal spousal support and K6 (pvalue = 0.031). This research is expected by officers at Kalike health center to carry out more optimal health promotion for families, communities and community leaders to motivate mothers to do ANC regularly. And the family / husband is expected to provide support to pregnant women to do regular pregnancy checks at least 6x during pregnancy.